2013
DOI: 10.1371/journal.pone.0065098
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Promotes Consolidation of Emotional Memory in Healthy Children but Not in Children with Attention-Deficit Hyperactivity Disorder

Abstract: Fronto-limbic brain activity during sleep is believed to support the consolidation of emotional memories in healthy adults. Attention deficit-hyperactivity disorder (ADHD) is accompanied by emotional deficits coincidently caused by dysfunctional interplay of fronto-limbic circuits. This study aimed to examine the role of sleep in the consolidation of emotional memory in ADHD in the context of healthy development. 16 children with ADHD, 16 healthy children, and 20 healthy adults participated in this study. Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
106
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(117 citation statements)
references
References 61 publications
9
106
1
Order By: Relevance
“…As recently shown, slow wave activity (SWA, 1e4.5 Hz) during SWS is altered in children suffering from ADHD: while over central positions the SWA was enhanced, it was attenuated by trend over frontal positions [35]. Our previous studies pointed to a reduced frontal brain function as the cause of the impaired memory consolidation during sleep in ADHD [34,36,37]. Therefore, the aim of the present study was to show that an enhancement of frontal SO activity at 0.75 Hz by toDCS during sleep enhances declarative memory consolidation in ADHD to a level comparable to that of healthy controls.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…As recently shown, slow wave activity (SWA, 1e4.5 Hz) during SWS is altered in children suffering from ADHD: while over central positions the SWA was enhanced, it was attenuated by trend over frontal positions [35]. Our previous studies pointed to a reduced frontal brain function as the cause of the impaired memory consolidation during sleep in ADHD [34,36,37]. Therefore, the aim of the present study was to show that an enhancement of frontal SO activity at 0.75 Hz by toDCS during sleep enhances declarative memory consolidation in ADHD to a level comparable to that of healthy controls.…”
Section: Introductionmentioning
confidence: 83%
“…In our previous studies, we controlled for sleep/wake states and observed deficits in sleep-dependent consolidation of long-term declarative memory (picture recognition) in ADHD. Most strikingly, reduced memory performance in ADHD after sleep was linked to SO activity during sleep [34,37].…”
Section: Discussionmentioning
confidence: 99%
“…(2) In opposition, the proportion of REM sleep in typically developing children (TDC) correlated negatively with inattention and positively with performance IQ (Kirov et al, 2011). Similarly, another recent study showed that whereas in youths with ADHD, theta (4–8 Hz) EEG power during REM sleep correlated negatively with emotional memory consolidation, in healthy individuals, this correlation was positive (Prehn-Kristensen et al, 2013). Collectively, these latter findings suggest at least a bi-directional role of REM sleep and its physiology, depending on presence or absence of ADHD psychopathology.…”
Section: Introductionmentioning
confidence: 84%
“…Theta EEG activity recorded from central cortical regions, related to face memory itself, should be distinguished from posterior theta activity, which is rather related to the processing of facial emotional expression (Guntekin & Basar, 2009). Frontal theta activity in REM sleep is positively correlated with emotional memory in typically-developing children, but the inverse is seen in children with attention deficit and hyperactivity disorder (Prehn-Kristensen et al, 2013).…”
mentioning
confidence: 93%
“…REM sleep (Fogel, Smith, & Beninger, 2009;Prehn-Kristensen et al, 2013). Sleep also improves recognition of neutral faces (M. A.…”
mentioning
confidence: 99%